Developing HOTS-Based Supplementary Reading Material for EFL Learners (Scripta : English Department Journal, 2023)
The objectives of this study were (1) to describe the students‘ needs of Grade XI of SMK Negeri 1 Karanganyar for HOTS-based supplementary reading material and (2) to develop the material in search of its appropriateness. The method of the research is Educational Research and Development (R&D)  proposed by Borg and Gall‘s model. The data were collected through questionnaires, interviews, and observation, and analyzed using descriptive statistics and descriptive qualitative methods. The subject of the research was 36 students selected in purposive sampling. The need analysis showed that the majority of students were eager to have HOTS-based reading material. Presented with the scientific approach, the developed material can facilitate HOTS students. The appropriateness of the product was achieved with a score of 3,78 meant appropriate.
Keywords: Accounting students; Higher-order thinking skills; Supplementary reading materials